Resistance of concrete protective coatings in different chemical environments - Bibi, Tayyaba (Penerbit UTM Press, 2015)
The objective of this research study was to introduce concrete protective coatings which provide maximum resistance against chemical attacks. The admixtures-silica fume and fly ash were also used to enhance the impermeability of concrete to a greater extent. Tests conducted at various stages of the curing process allowed us to study the destructive and non-destructive strengths of the specimens. The mortar samples were coated with three different types of epoxy coatings and bitumen. They were then subjected to different chemical environments by immersing them in 10% standard solutions of each ammonium nitrate, sodium chloride and sulphuric acid. Drop in strength as a result of chemical exposure was considered as a measure of chemical attack. This was achieved by measuring the drop in compressive strength after 14 and 28 days of chemical exposure. The compressive strength results following chemical exposure indicated that the samples containing silica fume and fly ash (5% replacement of each by weight of cement) and the protective coating Epoxy-2 (E-2) proved to be more resistant to attacks. The control sample (without admixtures) showed a much greater degree of deterioration. Therefore, the application of E-2 coating in addition to silica fume and fly ash was invariably much more effective in improving the compressive strength as well as the resistance of concrete against chemical attacks. The results also indicated that among all the aggressive attacks, the sulphate environment has the most adverse effect on concrete in terms of lowering its strength.